IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIM-RS) PADA RUMAH SAKIT UMUM DAERAH HARAPAN DAN DOA KOTA BENGKULU - Budiman Sakti; Sari, Fitri Yunita; Alexsander; Harmiati (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
This research aims to analyze the implementation of SIMRS at Harapan and Doa Hospital, Bengkulu City. This research uses a qualitative approach with data collection methods through observation, interviews and documentation. The interview process involved informants from the SIMRS management team and also elements of hospital leadership. The research results show that in terms of communication everything went well, SIMRS improved communication between service units in providing data and information. The resources chosen to manage SIMRS also come from the results of special recruitment according to the criteria which will later become the SIMRS IT team. The disposition of implementing this system has a positive influence which can be seen from the acceptance of implementing this system in the hospital environment. In terms of bureaucratic structure, the SIMRS management team only consists of several leadership elements and the IT team. Meanwhile, operators are not included in the SIMRS management structure. In conclusion, the implementation of the Hospital Management Information System (SIMRS) at Harapan Hospital and Bengkulu City is going well.